Is there a national variation in cardiothoracic trainees' satisfaction? Evaluation of the United Kingdom General Medical Council national training surveys. Issue 10 (7th August 2019) - Chan, Jeremy; Oo, Shwe; Yeatman, Mark
Abstract: Background: The national training surveys was first started in 2006, with an aim to determine the quality of the national training standard. All trainees working in a General Medical Council approved training post are required to complete the survey. We aimed to evaluate cardiothoracic trainees' satisfaction and determine whether there is variation in the United Kingdom. Method: The national training survey report in cardiothoracic surgery from 2012 to 2019 was obtained from the General Medical Council website. The cardiothoracic centers were divided based on their geographic locations. Comparisons in all 18 indicators in the national training surveys report were made between the four counties (national) and four local education training boards (LETBs) in England (Regional). Centers with less than 4 years of data were excluded from this study. Results: Thirty‐three cardiothoracic centers are included in this study The top three areas that trainees are most satisfied are clinical supervision (out of hours) (91.65), clinical supervision (90.65), and educational supervision (88.27). On the other hand, trainees are less satisfying with the handover (62.63), rota design (61.91), and workload (45.07). It is worth noting that workload is the only area of less than 60%. In addition, there is no national variation in all 18 indicators Conclusion: Our data suggested that there is no difference in overall trainee satisfaction in the United Kingdom. However, there are differences in various indicators between England and the three other nations. Individual hospital should reflect on trainees' evaluation on the national training surveys report and improve on specific areas if deemed unsatisfactory.